2000
DOI: 10.1002/1521-3803(20000701)44:4<233::aid-food233>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biochemical composition of caviar from different sturgeon species and origins

Abstract: The chemical and biochemical composition of caviar in 22 specimens of wild caught and of 2 farmed animals were measured. The results include grain size, protein and fat content, fatty acid composition of triglycerides and phospholipids, as well as the concentrations of relevant heavy metals and chlorinated hydrocarbons. The average protein content varied between 26.2 and 31.1% (wet weight) and fat from 10.9 to 19.4% (wet weight) with lowest values for caviar from farmed sturgeon. The triglycerides and phosphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 6 publications
7
42
0
Order By: Relevance
“…Bledsoe et al [11] determined the amount of moisture in raw roe obtained from salmon as 50%, and they reported that the moisture rate of the caviar differed according to the type of salmon, e.g., 50-60% in Oncorhynchus gorbuscha, 55-56% in Oncorhynchus keta, 56-58% in Oncorhynchus nerka, and 51-70% in Oncorhynchus ishawischa. Wirth et al [12] reported the moisture content in caviar obtained from sturgeon as 38-53%. Inal [13] declared the moisture in good-quality caviar as 45%.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Bledsoe et al [11] determined the amount of moisture in raw roe obtained from salmon as 50%, and they reported that the moisture rate of the caviar differed according to the type of salmon, e.g., 50-60% in Oncorhynchus gorbuscha, 55-56% in Oncorhynchus keta, 56-58% in Oncorhynchus nerka, and 51-70% in Oncorhynchus ishawischa. Wirth et al [12] reported the moisture content in caviar obtained from sturgeon as 38-53%. Inal [13] declared the moisture in good-quality caviar as 45%.…”
Section: Discussionmentioning
confidence: 90%
“…It did not change much during storage and was between 11.48 and 11.57% in 4% salted caviar and between 11.57 and 11.69% in 8% salted caviar. In another study, the fat amount was 10.9-19.4% in caviar obtained from salmon fish [12]. Himelbloom et al [15] detected 11% fat in their salmon caviar (ikura).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid heat treatment and 3% of NaCl may have contributed to the lower moisture content, resulting in the highest concentration of ash and energy content in the sample O. Wirth et al (2000) evaluated the composition of caviar from roes of wild and farmed sturgeons, resulting in protein contents of 26.2 to 31.1% and lipids of 19.4% to 10.9. The lowest values were found in caviar from roes of farmed sturgeons.…”
Section: Resultsmentioning
confidence: 99%
“…The low lipid contents obtained in the current study may be related to the diet composition, with 45% crude protein and 10% crude fat. The protein contents for the raw material and treatments are similar to those obtained by Wirth et al (2000) for caviar of farmed sturgeon. Caloric values obtained are within the limits proposed by Brunner, Marx, and Stolle (1995) for roes of various species, between 130 and 280 kcal 100 g -1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation